2016
DOI: 10.1097/bot.0000000000000501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implant Failure After Symphyseal Plating on Functional Outcome and General Health

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 27 publications
4
23
2
Order By: Relevance
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-eight studies [ 8 , 9 , 25 , 26 , 28 – 30 , 32 – 36 , 10 , 37 44 , 46 , 47 , 11 , 48 54 , 56 , 18 – 22 , 24 ] used a pelvic-specific PROM, either as a single instrument or in combination with a generic PROM. Generic PROMs for physical functioning and quality of life were used in 15 studies [ 8 , 10 , 39 , 40 , 46 , 57 , 58 , 12 , 13 , 15 , 17 , 19 , 23 , 27 , 30 ]. The follow-up moment when these questionnaires were assessed ranged from six months to 15 years after the injury.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 34 studies [ 8 , 9 , 26 , 28 – 30 , 32 37 , 10 , 39 , 41 , 43 , 44 , 46 51 , 11 , 52 54 , 19 – 22 , 24 , 25 ] that used the Majeed Pelvic Score (MPS), in 28 of them [ 9 , 11 , 32 – 38 , 41 , 43 , 44 , 20 , 47 54 , 21 , 22 , 24 26 , 28 , 29 ] it was the only outcome instrument used. Most studies described the results in terms of the clinical grade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though no patient reported outcome measures have been developed for pelvic trauma; generic outcome instruments (SF-36) and disease speci c instruments have been used to assess patient functional performance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Giannoudis et al found no correlation of its occurrence with worse functional outcome [14]. On the other hand, Frietman et al [25] retrospectively evaluated 37 patients treated with anterior pelvic plating and reported higher Majeed scores and similar SF-36 scores in patients with implant failure. Conversely, we observed signi cant differences in mean Majeed scores of patients with and without FF (p = 0,012).…”
Section: Discussionmentioning
confidence: 99%